Whole-crystalline molecular sieve catalyst and preparation method and application thereof
By adding rare earth elements and phosphorus elements to the fully crystallized molecular sieve catalyst, and using organic acid treatment and water vapor treatment, the problem of low catalyst crushing strength is solved, and the combination of high mechanical strength and good catalytic performance is achieved.
Patent Information
- Application Number
- CN202311036495.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-16
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-08-16
AI Technical Summary
The crushing strength of existing fully crystalline molecular sieve catalysts is poor, which is difficult to meet the mechanical strength requirements for industrial applications. At the same time, the activity and selectivity of the catalyst are also poor.
By optimizing the composition and preparation method of the catalyst, including adding an appropriate amount of rare earth elements and phosphorus elements to the catalyst, and adjusting the acid strength and structure through organic acid treatment and water vapor treatment, a fully crystallized ZSM-5 molecular sieve with high crushing strength was prepared. catalyst.
The crushing strength of the catalyst is significantly improved to reach 60-100N/5mm, and it shows good stability and selectivity in the propylene reaction to crack the carbon tetraolefin.
Smart Images

Figure CN119500239A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of molecular sieve catalyst preparation, and specifically relates to a fully crystalline molecular sieve catalyst and a preparation method and application thereof. Background Art
[0002] Zeolite molecular sieves are widely used in the field of catalysis because of their advantages such as uniform and ordered micropores, large specific surface area, and high hydrothermal stability. Zeolite powder is very inconvenient in practical applications due to its small particle size. It has disadvantages such as difficult recovery, easy deactivation and aggregation. Therefore, it needs to be pre-molded before use. During the molding process, a certain amount of binder is generally required to be added. The binder content generally accounts for 30% to 40% of the total weight of the catalyst, or even higher, so that the catalyst has a certain specific shape and a certain mechanical strength. From this point of view, the binder is necessary. However, the binder is generally an inert component. The addition of the binder actually has a "dilution" effect on the active center of the molecular sieve, which increases the actual reaction space velocity and accelerates the deactivation of the catalyst. In addition, the binder has a certain pore blocking effect on the molecular sieve and affects the diffusion performance. Fully crystalline molecular sieve refers to zeolite particles that do not contain inert binders, have high crystallinity, a large available effective surface area, and better catalytic performance. In addition, fully crystalline molecular sieves are actually the binders added during the molecular sieve molding process converted into effective components of molecular sieves, which is equivalent to the molded catalyst being all molecular sieves with pore structures. Compared with molecular sieve catalysts containing binders, the mechanical strength of fully crystalline molecular sieve catalysts will be reduced to a certain extent. This is a problem that must be faced and overcome in the industrial application of fully crystalline molecular sieve catalysts.
[0003] At present, the research on binders is mostly focused on silica and alumina. The aluminum atoms in the alumina binder enter the molecular sieve framework to increase the acid content of the molecular sieve. Similarly, the silica binder reduces its acid content and reduces its strength. Liu Hui et al. [Liu Hui, Wei Huijuan, Xin Wenjie, Liu Shenglin, Xie Sujuan, Xu Longya, Acta Petrolei Sinica (Petroleum Processing), 30 (2014) 115-120] reported that in the alkylation reaction of benzene and dimethyl ether, compared with the ZnZSM-11 catalyst with alumina binder, the catalyst with aluminum phosphate binder is more conducive to the conversion of benzene, promoting the methylation reaction of benzene while inhibiting the ethylation reaction of benzene.
[0004] If the binder is converted into a molecular sieve, it forms a catalytic material with a certain shape, size and mechanical strength together with the original molecular sieve, that is, a binderless molecular sieve catalyst, which can give full play to the reaction performance of the catalyst under the condition of ensuring the mechanical strength and acid content of the catalyst. The methods for synthesizing binderless molecular sieves include liquid-solid phase conversion method, gas-solid phase conversion method and assembly molding method, but in the actual synthesis process, due to various reasons such as improper condition control, the obtained binderless molecular sieve catalyst is either very poor in strength or even crushed, or the activity and selectivity of the catalyst are poor, and it is difficult to take both into account. Summary of the invention
[0005] In view of the problem that the fully crystalline molecular sieve catalyst in the prior art has poor crushing strength, the present invention provides a new high-strength fully crystalline molecular sieve catalyst and its preparation method and application. The catalyst is applied to the reaction of cracking C4 olefins to produce propylene, and has the advantages of high catalyst stability and good propylene selectivity.
[0006] The first aspect of the present invention provides a fully crystalline molecular sieve catalyst, wherein the catalyst, based on the weight of the catalyst, comprises the following components:
[0007] a) 90% to 99% ZSM-5 molecular sieve;
[0008] b) 0.1% to 5% of rare earth elements;
[0009] c) 0.02% to 5% of P element;
[0010] Among them, the mass ratio of rare earth elements to P elements is 1 to 3:1.
[0011] The ratio of the amount of medium-strong acid to the amount of weak acid in the catalyst is 0.3 to 1:1.
[0012] According to the present invention, the ratio of the amount of medium-strong acid to the amount of weak acid in the catalyst is 0.5 to 1:1.
[0013] According to the present invention, in the catalyst, the mass ratio of rare earth element to P element is 1 to 2:1.
[0014] According to the present invention, in the catalyst, the SiO2 / Al2O3 molar ratio of the ZSM-5 molecular sieve in component a) is 50 to 1000, preferably 100 to 1000.
[0015] According to the present invention, in the catalyst, the rare earth element in component b) includes at least one of La, Ce, Pr and Nd.
[0016] According to the present invention, the average crushing strength of the fully crystalline molecular sieve catalyst is 60-100 N / 5 mm, preferably 65-80 N / 5 mm. The mass content of the binder component in the fully crystalline molecular sieve is less than 3%.
[0017] According to the present invention, preferably, based on the weight of the catalyst, the catalyst comprises the following components:
[0018] a) 96% to 99% ZSM-5 molecular sieve;
[0019] b) 0.1% to 3% of rare earth elements;
[0020] c) 0.02% to 1% of P element.
[0021] A second aspect of the present invention provides a method for preparing the above catalyst, the method comprising the following steps:
[0022] a) uniformly mixing a first template, an aluminum source, a silicon source, and an alkali source, performing a first hydrothermal crystallization, and a first calcination to obtain a precursor I;
[0023] b) mixing the precursor I and the binder and then subjecting them to molding to obtain the precursor II;
[0024] c) subjecting the precursor II to a second hydrothermal crystallization in a second template vapor atmosphere, and a second calcination to obtain the precursor III;
[0025] d) ammonium exchange the precursor III and calcination for the third time to obtain the precursor IV;
[0026] e) loading the precursor IV with rare earth elements and calcining for the fourth time to obtain the precursor V;
[0027] f) loading the precursor V with phosphorus, and calcining for the fifth time to obtain the precursor VI;
[0028] g) treating the precursor VI with an organic acid and steam to obtain the catalyst.
[0029] According to the present invention, in step a), the first template comprises at least one of tetramethylammonium bromide, tetraethylammonium bromide, tetrapropylammonium bromide and tetrapropylammonium hydroxide. The aluminum source comprises at least one of aluminum nitrate, aluminum sulfate and sodium aluminate. The silicon source comprises at least one of water glass, silica sol and tetraethyl orthosilicate. The alkali source comprises at least one of sodium hydroxide and potassium hydroxide. The first template is NH4 + The aluminum source is calculated as Al2O3, the silicon source is calculated as SiO2, and the alkali source is calculated as OH - The molar ratio of NH4 + :Al2O3:SiO2:OH -: H2O = 0.1-0.5: 0.001-0.02: 1: 0.1-0.4: 5-10. The temperature of the first hydrothermal crystallization is 80-200°C, and the crystallization time is 30-100h. The hydrothermal crystallization equipment is preferably an autoclave. The pressure of the autoclave is not particularly limited and is autogenous pressure. After hydrothermal crystallization, water washing and drying are performed. The drying temperature is 80-120°C and the time is 10-20h. The temperature of the first calcination is 500-600°C and the time is 4-8h.
[0030] According to the present invention, in step b), the binder is aluminum oxide and / or silicon oxide. Preferably, the binder is aluminum oxide and silicon oxide. The weight ratio of the feed materials is precursor I: aluminum oxide: silicon oxide = 20-80: 2: 18-78.
[0031] According to the present invention, in step b), the forming is kneading forming. After the forming process, drying can be performed at a temperature of 80 to 120° C. for 5 to 10 hours.
[0032] According to the present invention, in step c), the temperature of the second hydrothermal crystallization is 130-200°C, and the crystallization time is 20-200h. The second template comprises at least one selected from ammonia, ethylenediamine, triethylamine, n-butylamine, hexamethylenediamine, tetrapropylammonium bromide and tetrapropylammonium hydroxide. Further, preferably, the molar ratio of the silicon source in terms of SiO2 to the second template is 1:0.2-0.6. Preferably, the second template is added in the form of an aqueous solution. The mass percentage of the second template aqueous solution is 10%-60%.
[0033] According to the present invention, in step c), the second calcination is carried out at a temperature of 500-600°C for 3-10 hours. Drying may be performed before the second calcination, preferably at 80-120°C for 5-10 hours.
[0034] According to the present invention, in step d), the ammonium exchange can be carried out by conventional methods. Preferably, the exchange is carried out at 80 to 90° C. with a 5 to 10% by weight aqueous ammonium salt solution. The ammonium salt is preferably ammonium nitrate. After the ammonium exchange, washing and drying can be carried out. The drying conditions are: drying temperature 80 to 120° C., drying time 8 to 10 hours. The temperature of the third roasting is 500 to 600° C., and the roasting time is 4 to 8 hours.
[0035] According to the present invention, the method of loading the rare earth element in step e) can be an impregnation method, that is, the precursor IV is impregnated in a rare earth source solution. The rare earth source is a nitrate containing a rare earth element. The impregnation time is 12 to 48 hours. After impregnation, drying can be performed. The drying temperature is 60 to 100° C. and the drying time is 10 to 20 hours. The temperature of the fourth calcination is 450 to 600° C. and the time is 6 to 10 hours.
[0036] According to the present invention, the method of loading phosphorus in step f) can be an impregnation method, that is, the precursor V is impregnated in a phosphorus source solution. The phosphorus source is phosphoric acid. The impregnation time is 10 to 30 hours. After impregnation, it can be dried. The drying temperature is 80 to 120° C. and the time is 10 to 20 hours. The temperature of the fifth calcination is 500 to 600° C. and the time is 4 to 8 hours.
[0037] According to the present invention, the organic acid in step g) is an organic weak acid. The organic acid includes at least one selected from acetic acid, oxalic acid, benzoic acid, sorbic acid, citric acid, and malic acid. The organic acid treatment method is to immerse the precursor VI in an organic acid solution. The concentration of the organic acid solution is 3wt% to 10wt%, preferably 5wt% to 8wt%. The temperature of the organic acid treatment is 200 to 300°C, and the treatment time is 1 to 10h.
[0038] According to the present invention, the steam treatment in step g) is carried out by placing the precursor VI in a steam environment at a temperature of 500-600° C. and a treatment time of 2-20 hours.
[0039] According to the present invention, preferably, in step g), organic acid treatment and water vapor treatment can be used alternately. After the organic acid treatment is completed, it is switched to water vapor treatment. One organic acid treatment and one water vapor treatment constitute one alternating treatment process. Preferably, the alternating treatment process can be performed 1 to 5 times.
[0040] According to the present invention, after the organic acid treatment and the water vapor treatment in step g), nitrogen purging and cooling are performed at a cooling rate of 10 to 30°C / min to 10 to 30°C.
[0041] According to the present invention, the catalyst in step g) is a fully crystalline molecular sieve catalyst. The average crushing strength of the fully crystalline molecular sieve catalyst is 60 to 100 N / 5 mm, preferably 65 to 80 N / 5 mm. The mass content of the binder component is less than 3%.
[0042] The third aspect of the present invention provides the use of the above catalyst or the catalyst prepared by the above method in the reaction of cracking C4 olefins to produce propylene.
[0043] According to the present invention, the reaction conditions include: reaction temperature of 500-600°C; reaction pressure of 0-1.0 MPa; C4 olefin weight space velocity of 1-20 h -1 , preferably 2 to 15 hours -1 .
[0044] At present, the methods for preparing fully crystalline molecular sieve catalysts include liquid-solid phase conversion method, gas-solid phase conversion method and assembly molding method. In the actual preparation process, due to the difficulty in controlling the conditions or the inappropriate selection of raw materials, the prepared fully crystalline molecular sieve catalyst has low crystallinity or low crushing strength, and is easy to break during use, resulting in a decrease in catalyst performance and affecting industrial applications.
[0045] Compared with the prior art, the present invention has significant advantages and outstanding effects, as follows:
[0046] (1) In the present invention, the catalyst comprises a molecular sieve, a rare earth element, and a P element, and the mass ratio of the rare earth element to the P element and the acid amount ratio of the medium-strong acid to the weak acid are limited to a fully crystalline catalyst, which overcomes the problem of low crushing strength of the catalyst and ensures that the catalyst has good catalytic reaction performance for cracking of C4 olefins to produce propylene.
[0047] (2) In the present invention, in the preparation method of the catalyst, the acid strength of the catalyst can be adjusted by treating it with an organic weak acid solution at medium to high temperatures, and the medium-strong acid center is further weakened. Further high-temperature steam treatment can stabilize the adjusted catalyst acid center. The prepared catalyst overcomes the problem of low catalyst crushing strength and ensures that the catalyst has good C4 olefin cracking to propylene reaction performance.
[0048] (3) In the present invention, the average crushing strength of the fully crystalline molecular sieve catalyst is 60-100N / 5mm, which is significantly better than the fully crystalline molecular sieve catalyst prepared by conventional methods, and has good stability and selectivity in the reaction of cracking C4 olefins to produce propylene. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 This is the NH3-TPD spectrum of the catalyst in Example 1.
[0050] Figure 2 This is the NH3-TPD spectrum of the catalyst of Comparative Example 1.
[0051] Figure 3 It is the XRD pattern of the catalyst of Example 1. DETAILED DESCRIPTION
[0052] The present invention will be further described below by way of examples, but the protection scope of the present invention is not limited by the examples.
[0053] In the present invention, the acid strength of the catalyst is tested by ammonia temperature-programmed desorption (NH3-TPD) technology. Specifically, the sample to be tested is first crushed into 20-40 meshes, 100 mg is weighed and loaded into a quartz sample tube, activated at 600°C for 1 hour in an activation furnace under a helium atmosphere, then cooled to 100°C, ammonia is introduced to adsorb to saturation, and then helium is purged at the same temperature for 1 hour to remove physically adsorbed ammonia, then the temperature is raised to 600°C at a heating rate of 10°C / min, and the desorbed tail gas is analyzed by a chromatographic thermal conductivity cell detector to record the NH3-TPD spectrum.
[0054] In the present invention, according to the NH3-TPD spectrum, there are desorption peaks in the low-temperature desorption zone of 100-200°C and the high-temperature desorption zone of 300-400°C. The desorption peak at 100-200°C represents the desorption of NH3 from the weak acid site on the surface of the molecular sieve, corresponding to the weak acid center of the molecular sieve. The desorption peak at 300-400°C represents the desorption of NH3 from the medium-strong acid site on the surface of the molecular sieve, corresponding to the medium-strong acid center of the molecular sieve. The NH3-TPD spectrum was fitted with a Gaussian curve, and the ratio of the medium-strong acid amount to the weak acid amount of the catalyst was calculated based on the ratio of the peak area of the medium-strong acid peak and the weak acid peak.
[0055] In the present invention, a particle strength tester is used to test the radial mechanical strength of the catalyst. 30 catalyst particles with a length of 5 mm are taken to measure their strengths, and the average value is taken as the average crushing strength of the catalyst.
[0056] In the present invention, the stability time in each example is recorded as X hours, which means that within X hours, the decrease rate of propylene yield is less than or equal to 3wt% / hour; after more than X hours, the catalyst activity decreases rapidly, and the decrease rate of propylene yield is greater than 3wt% / hour.
[0057] Example 1
[0058] a) Tetrapropylammonium hydroxide is used as the template, aluminum sulfate is used as the aluminum source, water glass is used as the silicon source, sodium hydroxide is used as the alkali source, and the template is NH4 + The aluminum source is calculated as Al2O3, the silicon source is calculated as SiO2, and the alkali source is calculated as OH - The molar ratio of NH4 to water is: + :Al2O3:SiO2:OH - : H2O = 0.2: 0.002: 1: 0.2: 8. The above raw materials are mixed and stirred evenly, then transferred into an autoclave and crystallized at 160°C for 40 hours. The synthesized product is washed with water, dried at 80°C for 20 hours, and calcined at 600°C for 4 hours to obtain ZSM-5 molecular sieve raw powder.
[0059] b) 300 g of the above molecular sieve powder, 8 g of alumina and 200 g of silica sol (SiO2 mass content of 40%) were mixed and kneaded, extruded into particles with a diameter of 3 mm, a length of 3-10 mm and a circular cross section, and dried at 100°C for 8 hours.
[0060] c) Add 50% ethylenediamine aqueous solution in a closed reactor at a molar ratio of silicon source to ethylenediamine of 1:0.2. Place the above particle sample on the reactor. Crystallize at 180°C for 30 hours. After the product is taken out, dry at 120°C for 8 hours and calcine at 550°C in a muffle furnace air atmosphere for 5 hours.
[0061] d) The calcined product of step c) is taken out and ion exchanged with a 10 wt% aqueous solution of ammonium nitrate at 90° C., washed, dried at 120° C. for 8 hours, and then calcined at 500° C. for 8 hours.
[0062] e) preparing a lanthanum nitrate solution containing 1.5 wt% of La, impregnating the solid for 20 hours, drying at 80° C. for 12 hours and then calcining at 500° C. for 6 hours.
[0063] f) preparing a phosphoric acid solution containing 0.5 wt% of P, impregnating the solid for 10 hours, drying at 100° C. for 15 hours, and then calcining at 550° C. for 5 hours.
[0064] g) Take 20 grams of the solid product, put it into a tube furnace, heat it to 200°C in a nitrogen atmosphere, switch to a 5% citric acid aqueous solution, treat it for 3 hours, switch to water vapor, heat it to 550°C, treat it for 3 hours, purge it with nitrogen for 3 hours, then cool it down to 200°C, repeat the above process once, and obtain a high-strength fully crystalline ZSM-5 molecular sieve catalyst. The NH3-TPD spectrum of the catalyst is shown in Figure 1 The XRD pattern of the catalyst is shown in Figure 3 The composition of the fully crystalline molecular sieve catalyst is shown in Table 1.
[0065] The prepared catalyst was evaluated for its performance in the cracking of 60 wt% C4 hydrocarbons to produce propylene using a fixed-bed catalytic reaction apparatus. The process conditions used were: reaction temperature of 550°C, reaction pressure of 0.02 MPa, and C4 olefin weight space velocity of 20 h -1 The test results are shown in Table 2.
[0066] Example 2
[0067] a) Tetramethylammonium bromide is used as template, aluminum nitrate is used as aluminum source, water glass is used as silicon source, sodium hydroxide is used as alkali source, and the template is NH4 + The aluminum source is calculated as Al2O3, the silicon source is calculated as SiO2, and the alkali source is calculated as OH - The molar ratio of NH4 to water is: +:Al2O3:SiO2:OH - : H2O = 0.2: 0.001: 1: 0.4: 5. The above raw materials are mixed and stirred evenly, then transferred into an autoclave and crystallized at 120°C for 50 hours. The synthesized product is washed with water, dried at 120°C for 10 hours, and calcined at 600°C for 4 hours to obtain ZSM-5 molecular sieve raw powder.
[0068] b) 300 g of the above molecular sieve powder, 30 g of alumina and 800 g of silica sol (SiO2 mass content of 40%) were mixed and kneaded, extruded into particles with a diameter of 3 mm, a length of 3-10 mm and a circular cross section, and dried at 80°C for 10 hours.
[0069] c) Add 50% triethylamine aqueous solution by mass into a closed reactor at a molar ratio of silicon source to triethylamine of 1:0.5. Place the above particle sample on the reactor. Crystallize at 130°C for 200 hours. After the product is taken out, dry it at 80°C for 10 hours and calcine it at 500°C in an air atmosphere of a muffle furnace for 10 hours.
[0070] d) The calcined product of step c) was taken out and ion exchanged with a 5 wt% aqueous solution of ammonium nitrate at 90° C., washed, dried at 80° C. for 10 hours, and then calcined at 600° C. for 4 hours.
[0071] e) preparing a lanthanum nitrate solution containing 3 wt% of La, impregnating the solid for 12 hours, drying at 100° C. for 10 hours, and then calcining at 500° C. for 6 hours.
[0072] f) preparing a phosphoric acid solution containing 1 wt% of P, impregnating the solid for 30 hours, drying at 80°C for 20 hours and calcining at 600°C for 4 hours.
[0073] g) Take 20 grams of the above solid product, put it into a tube furnace, heat it to 300°C in a nitrogen atmosphere, switch to a 3% oxalic acid aqueous solution, treat it for 3 hours, switch to water vapor, heat it to 600°C, treat it for 5 hours, purge it with nitrogen for 3 hours, then cool it to 300°C, repeat the above process once, and obtain a high-strength fully crystalline ZSM-5 molecular sieve catalyst. The composition of the fully crystalline molecular sieve catalyst is shown in Table 1.
[0074] The evaluation method and evaluation conditions are the same as those in Example 1. The evaluation results are shown in Table 2.
[0075] Example 3
[0076] a) Tetrapropylammonium bromide is used as template, aluminum nitrate is used as aluminum source, water glass is used as silicon source, potassium hydroxide is used as alkali source, and the template is NH4 + The aluminum source is calculated as Al2O3, the silicon source is calculated as SiO2, and the alkali source is calculated as OH - The molar ratio of NH4 to water is: +:Al2O3:SiO2:OH - : H2O = 0.2: 0.01: 1: 0.1: 10. The above raw materials are mixed and stirred evenly, then transferred into an autoclave and crystallized at 200°C for 30 hours. The synthesized product is washed with water, dried at 100°C for 8 hours, and calcined at 600°C for 5 hours to obtain ZSM-5 molecular sieve raw powder.
[0077] b) 600 g of the above molecular sieve powder, 60 g of alumina and 1500 g of silica sol (SiO2 mass content of 80%) were mixed and kneaded, extruded into particles with a diameter of 3 mm, a length of 3-10 mm and a circular cross section, and dried at 100°C for 8 hours.
[0078] c) Add 50% ammonia solution by mass into a closed reactor at a molar ratio of silicon source to ammonia (in terms of NH3) of 1:0.6. Place the above particle sample above the reactor. Crystallize at 130°C for 200 hours. After the product is taken out, dry it at 120°C for 8 hours and calcine it at 600°C in an air atmosphere of a muffle furnace for 3 hours.
[0079] d) The calcined product of step c) is taken out and ion exchanged with a 10 wt % aqueous solution of ammonium nitrate at 80° C., washed, dried at 100° C. for 8 hours, and then calcined at 500° C. for 8 hours.
[0080] e) preparing a lanthanum nitrate solution containing 0.1 wt% of La, impregnating the solid for 20 hours, drying at 80° C. for 15 hours and then calcining at 500° C. for 6 hours.
[0081] f) preparing a phosphoric acid solution containing 0.05 wt% of P, impregnating the solid for 10 hours, drying at 100° C. for 12 hours, and then calcining at 550° C. for 5 hours.
[0082] g) Take 20 grams of the above solid product, put it into a tube furnace, heat it to 250°C in a nitrogen atmosphere, switch to 8% acetic acid aqueous solution, treat it for 1 hour, switch to water vapor, heat it to 600°C, treat it for 2 hours, purge it with nitrogen for 3 hours, then cool it to 250°C, repeat the above process once. Take out the sample to obtain a high-strength fully crystalline ZSM-5 molecular sieve catalyst. The composition of the fully crystalline molecular sieve catalyst is shown in Table 1.
[0083] The evaluation method and evaluation conditions are the same as those in Example 1. The evaluation results are shown in Table 2.
[0084] Example 4
[0085] a) Tetramethylammonium bromide is used as template, aluminum sulfate is used as aluminum source, silica sol is used as silicon source, sodium hydroxide is used as alkali source, and the template is NH4 + The aluminum source is calculated as Al2O3, the silicon source is calculated as SiO2, and the alkali source is calculated as OH - The molar ratio of NH4 to water is:+ :Al2O3:SiO2:OH - : H2O = 0.5: 0.02: 1: 0.1: 6. The above raw materials are mixed and stirred evenly, then transferred into an autoclave and crystallized at 80°C for 100 hours. The synthesized product is washed with water, dried at 80°C for 20 hours, and calcined at 600°C for 4 hours to obtain ZSM-5 molecular sieve raw powder.
[0086] b) 300 g of the above molecular sieve powder, 20 g of alumina and 600 g of silica sol (SiO2 mass content of 80%) were mixed and kneaded, extruded into particles with a diameter of 3 mm, a length of 3-10 mm and a circular cross section, and dried at 100°C for 8 hours.
[0087] c) Add 50% by mass of tetrapropylammonium hydroxide aqueous solution into a closed reactor at a molar ratio of silicon source to tetrapropylammonium hydroxide of 1:0.5. Place the above particle sample on the reactor and crystallize at 180°C for 30 hours. After the product is taken out, dry it at 120°C for 8 hours and calcine it at 550°C in a muffle furnace air atmosphere for 5 hours.
[0088] d) The calcined product of step c) is taken out and ion exchanged with a 10 wt% aqueous solution of ammonium nitrate at 90° C., washed, dried at 120° C. for 8 hours, and then calcined at 500° C. for 8 hours.
[0089] e) preparing a lanthanum nitrate solution containing 2 wt% of La, impregnating the solid for 20 hours, drying at 80° C. for 12 hours, and then calcining at 500° C. for 6 hours.
[0090] f) preparing a phosphoric acid solution containing 2 wt% of P, impregnating the solid for 10 hours, drying at 100° C. for 15 hours and calcining at 550° C. for 5 hours.
[0091] g) Take 20 grams of the above solid product, put it into a tube furnace, heat it to 200°C in a nitrogen atmosphere, switch to a 7% citric acid aqueous solution, treat it for 3 hours, switch to water vapor, heat it to 550°C, treat it for 3 hours, purge it with nitrogen for 3 hours, then cool it to 200°C, repeat the above process once, and obtain a high-strength fully crystalline ZSM-5 molecular sieve catalyst. The composition of the fully crystalline molecular sieve catalyst is shown in Table 1.
[0092] The evaluation method and evaluation conditions are the same as those in Example 1. The evaluation results are shown in Table 2.
[0093] Comparative Example 1
[0094] The difference from Example 1 is that neither carboxylic acid nor steam post-treatment is used, specifically:
[0095] a) Tetrapropylammonium hydroxide is used as the template, aluminum sulfate is used as the aluminum source, water glass is used as the silicon source, sodium hydroxide is used as the alkali source, and the template is NH4+ The aluminum source is calculated as Al2O3, the silicon source is calculated as SiO2, and the alkali source is calculated as OH - The molar ratio of NH4 to water is: + :Al2O3:SiO2:OH - : H2O = 0.2: 0.002: 1: 0.2: 8. The above raw materials are mixed and stirred evenly, then transferred into an autoclave and crystallized at 160°C for 40 hours. The synthesized product is washed with water, dried at 80°C for 20 hours, and calcined at 600°C for 4 hours to obtain ZSM-5 molecular sieve raw powder.
[0096] b) 300 g of the above molecular sieve powder, 8 g of alumina and 200 g of silica sol (SiO2 mass content of 40%) were mixed and kneaded, extruded into particles with a diameter of 3 mm, a length of 3-10 mm and a circular cross section, and dried at 100°C for 8 hours.
[0097] c) Add 50% ethylenediamine aqueous solution in a closed reactor at a molar ratio of silicon source to ethylenediamine of 1:0.2. Place the above particle sample on the reactor and crystallize at 180°C for 30 hours. After the product is taken out, dry it at 120°C for 8 hours and calcine it at 550°C in a muffle furnace air atmosphere for 5 hours.
[0098] d) The calcined product of step c) is taken out and ion exchanged with a 10 wt % aqueous solution of ammonium nitrate at 90° C., washed, dried at 120° C. for 8 h, and then calcined at 500° C. for 8 h.
[0099] e) preparing a lanthanum nitrate solution containing 1.5 wt% of La, impregnating the solid for 20 hours, drying at 80° C. for 12 hours, and then calcining at 500° C. for 6 hours.
[0100] f) preparing a phosphoric acid solution containing 0.5 wt% of P, impregnating the solid for 10 hours, drying at 100°C for 15 hours, and then calcining at 550°C for 5 hours to obtain a fully crystalline ZSM-5 molecular sieve catalyst. The NH3-TPD spectrum of the catalyst is shown in Figure 2 The composition of the fully crystalline molecular sieve catalyst is shown in Table 1.
[0101] The evaluation method and evaluation conditions are the same as those in Example 1. The evaluation results are shown in Table 2.
[0102] Comparative Example 2
[0103] The difference from Example 1 is that only organic acid post-treatment is used without water vapor post-treatment, specifically:
[0104] a) Tetrapropylammonium hydroxide is used as the template, aluminum sulfate is used as the aluminum source, water glass is used as the silicon source, sodium hydroxide is used as the alkali source, and the template is NH4 + The aluminum source is calculated as Al2O3, the silicon source is calculated as SiO2, and the alkali source is calculated as OH -The molar ratio of NH4 to water is: + :Al2O3:SiO2:OH - : H2O = 0.2: 0.002: 1: 0.2: 8. The above raw materials are mixed and stirred evenly, then transferred into an autoclave and crystallized at 160°C for 40 hours. The synthesized product is washed with water, dried at 80°C for 20 hours, and calcined at 600°C for 4 hours to obtain ZSM-5 molecular sieve raw powder.
[0105] b) 300 g of the above molecular sieve powder, 8 g of alumina and 200 g of silica sol (SiO2 mass content of 40%) were mixed and kneaded, extruded into particles with a diameter of 3 mm, a length of 3-10 mm and a circular cross section, and dried at 100°C for 8 hours.
[0106] c) Add 50% ethylenediamine aqueous solution in a closed reactor at a molar ratio of silicon source to ethylenediamine of 1:0.2. Place the above particle sample on the reactor and crystallize at 180°C for 30 hours. After the product is taken out, dry it at 120°C for 8 hours and calcine it at 550°C in a muffle furnace air atmosphere for 5 hours.
[0107] d) The calcined product of step c) is taken out and ion exchanged with a 10 wt % aqueous solution of ammonium nitrate at 90° C., washed, dried at 120° C. for 8 h, and then calcined at 500° C. for 8 h.
[0108] e) preparing a lanthanum nitrate solution containing 1.5 wt% of La, impregnating the solid for 20 hours, drying at 80° C. for 12 hours, and then calcining at 500° C. for 6 hours.
[0109] f) preparing a phosphoric acid solution containing 0.5 wt% of P, impregnating the solid for 10 hours, drying at 100° C. for 15 hours, and then calcining at 550° C. for 5 hours.
[0110] g) Take 20 grams of the above solid product, put it into a tube furnace, heat it to 200°C in a nitrogen atmosphere, switch to a 5% citric acid aqueous solution, treat it for 6 hours, switch to nitrogen purge for 3 hours and then cool it to 200°C. Take out the sample to obtain a fully crystalline ZSM-5 molecular sieve catalyst. The average crushing strength of the catalyst is 50N / 5mm, and the ratio of medium-strong acid to weak acid in the catalyst is 1.5:1. The composition of the fully crystalline molecular sieve catalyst is shown in Table 1.
[0111] The evaluation method and evaluation conditions are the same as those in Example 1. The evaluation results are shown in Table 2.
[0112] Comparative Example 3
[0113] The difference from Example 1 is that no organic acid is used but only water vapor is used for post-treatment, specifically:
[0114] a) Tetrapropylammonium hydroxide is used as the template, aluminum sulfate is used as the aluminum source, water glass is used as the silicon source, sodium hydroxide is used as the alkali source, and the template is NH4 + The aluminum source is calculated as Al2O3, the silicon source is calculated as SiO2, and the alkali source is calculated as OH - The molar ratio of NH4 to water is: + :Al2O3:SiO2:OH - : H2O = 0.2: 0.002: 1: 0.2: 8. The above raw materials are mixed and stirred evenly, then transferred into an autoclave and crystallized at 160°C for 40 hours. The synthesized product is washed with water, dried at 80°C for 20 hours, and calcined at 600°C for 4 hours to obtain ZSM-5 molecular sieve raw powder.
[0115] b) 300 g of the above molecular sieve powder, 8 g of alumina and 200 g of silica sol (SiO2 mass content of 40%) were mixed and kneaded, extruded into particles with a diameter of 3 mm, a length of 3-10 mm and a circular cross section, and dried at 100°C for 8 hours.
[0116] c) Add 50% by mass ethylenediamine aqueous solution into a closed reactor at a molar ratio of silicon source to ethylenediamine of 1:0.2, place the above particle sample on the reactor, and crystallize for 30 hours at 180°C. After the product is taken out, dry it at 120°C for 8 hours, and calcine it at 550°C in an air atmosphere of a muffle furnace for 5 hours.
[0117] d) The calcined product of step c) is taken out and ion exchanged with a 10 wt % aqueous solution of ammonium nitrate at 90° C., washed, dried at 120° C. for 8 h, and then calcined at 500° C. for 8 hours.
[0118] e) preparing a lanthanum nitrate solution containing 1.5 wt% of La, impregnating the solid for 20 hours, drying at 80° C. for 12 hours, and then calcining at 500° C. for 6 hours.
[0119] f) preparing a phosphoric acid solution containing 0.5 wt% of P, impregnating the solid for 10 hours, drying at 100° C. for 15 hours, and then calcining at 550° C. for 5 hours.
[0120] g) Take 20 grams of the above solid product, put it into a tube furnace, heat it to 550°C in a nitrogen atmosphere, switch to water vapor, treat it for 6 hours, switch to nitrogen purge for 3 hours, cool it down, take out the sample, and obtain a fully crystalline ZSM-5 molecular sieve catalyst. The composition of the fully crystalline molecular sieve catalyst is shown in Table 1.
[0121] The evaluation method and evaluation conditions are the same as those in Example 1. The evaluation results are shown in Table 2.
[0122] Comparative Example 4
[0123] The difference from Example 1 is that the catalyst does not contain rare earth and phosphorus, specifically:
[0124] a) Tetrapropylammonium hydroxide is used as the template, aluminum sulfate is used as the aluminum source, water glass is used as the silicon source, sodium hydroxide is used as the alkali source, and the template is NH4 + The aluminum source is calculated as Al2O3, the silicon source is calculated as SiO2, and the alkali source is calculated as OH - The molar ratio of NH4 to water is: + :Al2O3:SiO2:OH - : H2O = 0.2: 0.002: 1: 0.2: 8. The above raw materials are mixed and stirred evenly, then transferred into an autoclave and crystallized at 160°C for 40 hours. The synthesized product is washed with water, dried at 80°C for 20 hours, and calcined at 600°C for 4 hours to obtain ZSM-5 molecular sieve raw powder.
[0125] b) 300 g of the above molecular sieve powder, 8 g of alumina and 200 g of silica sol (SiO2 mass content of 40%) were mixed and kneaded, extruded into particles with a diameter of 3 mm, a length of 3-10 mm and a circular cross section, and dried at 100°C for 8 hours.
[0126] c) Add 50% ethylenediamine aqueous solution in a closed reactor at a molar ratio of silicon source to ethylenediamine of 1:0.2. Place the above particle sample on the reactor and crystallize at 180°C for 30 hours. After the product is taken out, dry it at 120°C for 8 hours and calcine it at 550°C in a muffle furnace air atmosphere for 5 hours.
[0127] d) The calcined product of step c) is taken out and ion exchanged with a 10 wt % aqueous solution of ammonium nitrate at 90° C., washed, dried at 120° C. for 8 h, and then calcined at 500° C. for 8 hours.
[0128] e) Take 20 grams of the above solid product, put it into a tube furnace, heat it to 200°C in a nitrogen atmosphere, switch to a 5% citric acid aqueous solution, treat it for 3 hours, switch to water vapor, heat it to 550°C, treat it for 3 hours, purge it with nitrogen for 3 hours, then cool it to 200°C, repeat the above process once. Take out the sample to obtain a fully crystalline ZSM-5 molecular sieve catalyst. The composition of the fully crystalline molecular sieve catalyst is shown in Table 1.
[0129] The evaluation method and evaluation conditions are the same as those in Example 1. The evaluation results are shown in Table 2.
[0130] Comparative Example 5
[0131] The difference from Example 1 is that in step e), a lanthanum nitrate solution containing 1.6 wt% of La is prepared, and in step f), a phosphoric acid solution containing 0.4 wt% of P is prepared. Others are the same as in Example 1. The catalyst composition is shown in Table 1, and the test results are shown in Table 2.
[0132] From the comparison between Example 1 and Comparative Examples 1 to 4, it can be seen that the catalyst of the present invention is the result of the combined action of rare earth loading, phosphorus, organic acid post-treatment and water vapor post-treatment. When the catalyst does not contain rare earth and phosphorus, organic acid post-treatment and water vapor post-treatment cannot achieve the purpose of the present invention.
[0133] Table 1 Catalyst composition of each example
[0134] Component a), % Component b), % Component c), % Binder components Example 1 98 1.5 0.5 0 Example 2 96 3 1 0 Example 3 99.85 0.1 0.05 0 Example 4 96 2 2 0 Comparative Example 1 98 1.5 0.5 0 Comparative Example 2 98 1.5 0.5 0 Comparative Example 3 98 1.5 0.5 0 Comparative Example 4 100 0 0 0 Comparative Example 5 98 1.6 0.4 0
[0135] Table 2 Test results of various catalysts
[0136]
[0137] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A fully crystalline molecular sieve catalyst, based on the weight of the catalyst, comprising the following components: a) 90% to 99% ZSM-5 molecular sieve; b) 0.1% to 5% of rare earth elements; c) 0.02% to 5% of P element; in, The mass ratio of rare earth elements to P elements is 1 to 3:
1. The ratio of the amount of medium-strong acid to the amount of weak acid in the catalyst is 0.3 to 1:
1.
2. The catalyst according to claim 1, characterized in that In the catalyst, the mass ratio of rare earth element to P element is 1-2:1; and / or the ratio of the amount of medium-strong acid to the amount of weak acid is 0.5-1:
1.
3. The catalyst according to claim 1, characterized in that Component a) The SiO2 / Al2O3 molar ratio of the ZSM-5 molecular sieve is 50 to 1000, preferably 100 to 1000.
4. The catalyst according to claim 1, characterized in that Component b) The rare earth element includes at least one of La, Ce, Pr and Nd.
5. A method for preparing the catalyst according to any one of claims 1 to 4, comprising the following steps: a) uniformly mixing a first template, an aluminum source, a silicon source, and an alkali source, performing a first hydrothermal crystallization, and a first calcination to obtain a precursor I; b) mixing the precursor I and the binder and then subjecting them to molding to obtain the precursor II; c) subjecting the precursor II to a second hydrothermal crystallization in a second template vapor atmosphere, and a second calcination to obtain the precursor III; d) ammonium exchange the precursor III and calcination for the third time to obtain the precursor IV; e) loading the precursor IV with rare earth elements and calcining for the fourth time to obtain the precursor V; f) loading the precursor V with phosphorus, and calcining for the fifth time to obtain the precursor VI; g) treating the precursor VI with an organic acid and steam to obtain the catalyst.
6. The preparation method according to claim 5, characterized in that: In step a), The first template comprises at least one of tetramethylammonium bromide, tetraethylammonium bromide, tetrapropylammonium bromide and tetrapropylammonium hydroxide; And / or, the aluminum source includes at least one of aluminum nitrate, aluminum sulfate and sodium aluminate; And / or, the silicon source includes at least one of water glass, silica sol and tetraethyl orthosilicate; And / or, the alkali source includes at least one of sodium hydroxide and potassium hydroxide; And / or, the first template is NH4 + The aluminum source is calculated as Al2O3, the silicon source is calculated as SiO2, and the alkali source is calculated as OH - The molar ratio of NH4 + :Al2O3:SiO2:OH - : H2O=0.1~0.5: 0.001~0.02: 1: 0.1~0.4: 5~10.
7. The preparation method according to claim 5, characterized in that: In step a), the temperature of the first hydrothermal crystallization is 80-200° C., and the crystallization time is 30-100 h; And / or, the first calcination temperature is 500-600° C. and the time is 4-8 hours.
8. The preparation method according to claim 5, characterized in that: In step b), the binder is aluminum oxide and / or silicon oxide; Preferably, the binder is aluminum oxide and silicon oxide; the weight ratio of the feed is precursor I: Alumina:silicon oxide=20~80:2:18~78.
9. The preparation method according to claim 5, characterized in that: In step c), The second template agent includes at least one selected from ammonia water, ethylenediamine, triethylamine, n-butylamine, hexamethylenediamine, tetrapropylammonium bromide and tetrapropylammonium hydroxide; and / or, the temperature of the second hydrothermal crystallization is 130-200° C., and the crystallization time is 20-200 h; And / or, the temperature of the second calcination is 500-600° C., and the time is 3-10 hours.
10. The preparation method according to claim 5, characterized in that: In step g), the organic acid comprises at least one selected from acetic acid, oxalic acid, benzoic acid, sorbic acid, citric acid, and malic acid; And / or, the temperature of the organic acid treatment is 200-300° C., and the treatment time is 1-10 hours.
11. The preparation method according to claim 5, characterized in that: In step g), the temperature of the water vapor treatment is 500-600° C., and the treatment time is 2-20 hours.
12. Use of the catalyst according to any one of claims 1 to 4 or the catalyst prepared by the preparation method according to any one of claims 5 to 11 in the reaction of cracking C4 olefins to produce propylene.
Citation Information
Patent Citations
Catalyst for use in preparation of propylene by olefin cracking
CN102069007A
Lanthanum-phosphorus double-heteroatom ZSM-5 molecular sieve catalyst and preparation method thereof
CN103071523A
Aromatic hydrocarbon olefin removal catalyst, preparation method and application thereof
CN112657544A
ZSM-5 catalyst with micropores and mesopores, preparation method thereof and production method of light olefins through catalytic cracking of hydrocarbons using the catalyst
KR1020130134064A
ZSM-5 catalyst with micropores and mesopores, preparation method thereof and production method of light olefins through catalytic cracking of hydrocarbons using the catalyst
US20130085311A1